[Mrs. Istvan Kékesi 1.]
lady with hat walking on the bank of the Danube, rowing, cooking at camp-fire, cows, dance on the bank of the Danube and on therrace of the restaurant, photo making, wooden-slide, big ship &boat with little engine on the Danube, Gyula Gömbös gives a speech